TGT learning model assisted by puzzle on students' learning outcomes in the excretory system - Khairi Azkia Fazra Br. Berutu; Efrida Pima Sari Tambunan (Inovasi Kurikulum, 2025)
Biology learning in the schools studied still relies on conventional methods, which result in low student participation and learning outcomes. This provides a crucial foundation for researching to develop a more interactive and effective learning model. This study aims to examine the effect of implementing the Team Games Tournament (TGT) learning model combined with puzzle media on student learning outcomes in the excretory system material in senior high schools (SMA/MA). The research method employed is a quantitative approach with a quasi-experimental design, specifically a pretest-posttest control group design. The study population consisted of all students in grade XI IPA, with sampling conducted using a cluster random sampling technique. The students were divided into an experimental class (receiving implementation of TGT with puzzle media) and a control class (receiving the conventional method). The research instrument was a learning outcome test given before and after the treatment. The results showed a significant difference between the two groups. The average posttest score of the experimental class was higher than that of the control class. An independent t-test revealed that the TGT model, assisted by puzzles, had a positive effect on learning outcomes. Thus, the application of the TGT model with puzzle media has proven effective in increasing active participation, motivation, and student learning outcomes in the excretory system material.   Abstrak Pembelajaran Biologi pada sekolah yang diteliti masih banyak menggunakan metode konvensional yang menyebabkan rendahnya partisipasi dan hasil belajar peserta didik. Hal ini menjadi dasar penting dilaksanakannya penelitian untuk mencari model pembelajaran yang lebih interaktif dan efektif. Penelitian ini bertujuan untuk mengkaji pengaruh penerapan model pembelajaran Team Games Tournament (TGT) yang dipadukan dengan media puzzle terhadap hasil belajar peserta didik pada materi sistem ekskresi di SMA/MA. Metode penelitian yang digunakan adalah pendekatan kuantitatif dengan desain eksperimen semu tipe pretest-posttest control group design. Populasi penelitian adalah seluruh peserta didik kelas XI IPA, dengan pengambilan sampel menggunakan teknik cluster random sampling yang membagi peserta didik ke dalam kelas eksperimen (penerapan TGT dengan media puzzle) dan kelas kontrol (metode konvensional). Instrumen penelitian berupa tes hasil belajar yang diberikan sebelum dan sesudah perlakuan. Hasil penelitian menunjukkan adanya perbedaan signifikan antara kedua kelompok. Rata-rata nilai posttest kelas eksperimen lebih tinggi dibandingkan kelas kontrol. Uji t independen menunjukkan bahwa model TGT berbantuan puzzle berpengaruh positif terhadap hasil belajar. Dengan demikian, penerapan model TGT dengan media puzzle terbukti efektif dalam meningkatkan partisipasi aktif, motivasi, dan hasil belajar peserta didik pada materi sistem ekskresi. Kata Kunci: hasil belajar; media puzzle; model team games tournament; sistem ekskresi; TGT